If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-3=3/4(2x+12
We move all terms to the left:
3x-3-(3/4(2x+12)=0
Domain of the equation: 4(2x+12)-3!=0We multiply all the terms by the denominator
We move all terms containing x to the left, all other terms to the right
4(2x+12)!=3
x∈R
3x*4(2x+12)-3-(3=0
We add all the numbers together, and all the variables
3x*4(2x+12)=0
Wy multiply elements
12x^2(2=0
| -4(r+7)=-50 | | 7/r+3=11 | | 12x+9=27 | | 105=5(1-5n) | | 3x^2+405x-534600=0 | | x/3-1=40 | | X+5/10=x-12/9 | | 8c=5c+2- | | 4x-5=2(.5x+2) | | -3m^2-7m-10=0 | | 3(-10m-3)+6m=75 | | 36+42=2(11)+4h+3h+2 | | 4¼c=9¾c+44 | | 12t+6=90 | | (10x^2)-14x=0 | | 35+75=3x+7 | | 5x+7-2x=8+x-2 | | 4-5x+2x+25=180 | | 3x+5=9x/2=5x-1 | | 42=7x+2x+6 | | 11q²-44=0 | | 5=p5 | | -3.8(1-2.9p)=3.5p+15.752 | | -5(-6-4x)=6x+30 | | |n-7|=3n-1 | | 5/7w=4 | | 16y+4=100 | | 30x=11x+30 | | ?x7x?=231 | | 4(x+2)-9x=x-3(2x+1)-1 | | 3/5y+8=2/5y-2 | | 5=p÷5 |